Projects as a policy tool: a policy ethnographic investigation in the field of education in Sweden - Jan Gustafsson (Taylor & Francis Group, 2017)
Politics and educational policy have been increasingly projectified, and projects as an organisational form have become a symbol for solving complex educational problems and interventions. The present article is a policy ethnographic case study in the field of education in Sweden, concerning the use of projects as a policy tool in the Mountain School. The analytical focus is on using projects as a policy tool within a multi-project organisation, where the projects are aimed at promoting integration of pupils with immigrant backgrounds and improving their school achievements. Through the analysis I identified four distinct themes: Outward leadership and teacher teams, The projects have never belonged to the teachers, The lack of a common educational policy and Project as vision and reality. These four themes demonstrate the complexities and difficulties in relation to organisation, management, definition and implementation. These complexities and difficulties in the policy process are not unique to either regular or temporary organisations. However, what becomes apparent in the case of the Mountain School is that the number of projects was very high, which puts considerable pressure on the headmasters and the teachers in their decoding, interpreting, negotiating and enactment of project as a policy tool.